2006
DOI: 10.5860/crl.67.5.446
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Cross-Disciplinary Information Use by Author Affiliation: Demonstration of a Method

Abstract: In this paper, we report the results of a bibliometric study in which we track cross-disciplinary citation behavior in the sciences. We hypothesize that cross-disciplinary citation in the sciences increased over the time period 1985–2000. Unlike most previous studies in this area, we assign discipline to a paper by its first author’s affiliation, and we hypothesize that assigning papers to disciplines based on first-author affiliation would yield results consistent with previous findings on cross-disciplinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…The authors were particularly interested in those citations that crossed the discipline boundaries between biology, chemistry, and physics. Ortega and Antell (2006) found that, contrary to their expectations, cross-disciplinary citations rates remained between 30 to 45 percent throughout the period. There were a few changes.…”
Section: Abstract Citation Analysis Literature Reviewcontrasting
confidence: 72%
See 1 more Smart Citation
“…The authors were particularly interested in those citations that crossed the discipline boundaries between biology, chemistry, and physics. Ortega and Antell (2006) found that, contrary to their expectations, cross-disciplinary citations rates remained between 30 to 45 percent throughout the period. There were a few changes.…”
Section: Abstract Citation Analysis Literature Reviewcontrasting
confidence: 72%
“…It would be interesting to know whether a longitudinal study using her techniques would show changes to these patterns and whether similar trends are present in the humanities and social sciences. Ortega and Antell (2006) also used citation analysis to examine scholars' communication patterns. They looked at the published works of researchers in the sciences and assessed how often those in one academic department cited scholars in another department.…”
Section: Abstract Citation Analysis Literature Reviewmentioning
confidence: 99%
“…The distances are calculated by combining different factors which have been employed in R&D evaluation and management for a long time, such as the results of (co-)citation [45,57,58], co-authorship [8,53], co-applicant and co-word analyses [46]. Additional proxies to be used are classifications regarding keywords, subject area, journal topics and IPCs or SIC codes.…”
Section: Developing a Comprehensive Monitoring Conceptmentioning
confidence: 99%
“…The degree of convergence should eventually be calculated by combining different factors which have been employed in R&D evaluation and management for a long time, such as the results of (co-)citation (Meyer et al, 2008, Porter and Chubin, 1985, Rinia et al, 2002, co-authorship (Butcher andJeffrey, 2005, Ortega andAntell, 2006), co-applicant and co-word analyses (Moed, 2005). Additional proxies to be used are classifications regarding keywords, subject area, journal topics and IPCs (International Patent Classification) or SIC (Standard Industrial Classification) codes.…”
Section: Industry Convergencementioning
confidence: 99%